Effects of Different Operating Temperatures on the Tensile Properties of the Grid Plate Hardfaced with Colmonoy in a Pool Type Sodium Fast Reactor - S. Balaguru; Vela Murali; P. Chellapandi (Science and Technology of Nuclear Installations)
In sodium-cooled fast reactors (SFRs), the grid plate is a critical component which is made of 316 L(N) SS. It is supported on a core support structure which is also made of 316 L(N) SS. This assembly is immersed in a pool of sodium which acts as a coolant. If there is a direct contact between the grid plate and the flange of core support structure, self-welding takes place between them at the high operating temperature of SFR by a thin sheet of liquid sodium which gets into the gap between them as this sodium acts as a metallic gum. To avoid self-welding, the bottom plate of the grid plate is hardfaced with Colmonoy 5 by PTAW so that the direct contact between those two components is avoided. Due to the difference in coefficients of thermal expansion between the base metal and the coating, the interface is subjected to tensile force which may weaken the bonding strength between them at higher temperatures. Therefore, the weldment should be able to withstand the tensile force at higher operating temperatures for which hot tensile properties of the base metal and the weldment have been determined to study the compatibility between them after hardfacing for the reliable operation of SFR.